PENDAMPINGAN PEMBUATAN NOMOR INDUK BERUSAHA UNTUK KOPERASI UNIT DESA TANI MAKMUR SENDURO LUMAJANG - Muhammad Ichwanus Surur; Imam Bayhaki; Mochammad Afifuddin ('Ibadatuna : Jurnal Pengabdian Masyarakat, 2026)
This Community Service Program (PKM/KKN) aimed to provide assistance to a Village Unit Cooperative (Koperasi Unit Desa/KUD) in obtaining a Business Identification Number (Nomor Induk Berusaha/NIB) as an effort to strengthen business legality. The main problems faced by the cooperative were the absence of an NIB and the limited understanding of cooperative management regarding business licensing procedures through the Online Single Submission (OSS) system. The method applied in this program employed a participatory and educational approach through several stages, including preparation, socialization, technical assistance, and evaluation. The assistance was carried out directly by guiding cooperative administrators in preparing administrative documents, creating an OSS account, and completing the required data until the issuance of the NIB. The results showed that the assistance successfully facilitated the issuance of an NIB for the Village Unit Cooperative and improved the administrators’ understanding and capacity in managing business legality administration. In addition, there was an increased awareness of the importance of business legality to support the sustainability and development of the cooperative. This program is expected to serve as a model for business legality assistance that can be implemented in other village cooperatives to support rural economic empowerment.